INTEGRASI PENGENDALIAN INTERNAL PADA BADAN LAYANAN UMUM DAERAH (BLUD) PUSKESMAS - Maduratna, Enggal Sari (JURNAL PARADIGMA (PEMBERDAYAAN & PENGABDIAN KEPADA MASYARAKAT), 2024)
The Indonesian government issued regulations regarding the transition of community health centers to regional public service agencies (BLUDs) in 2018. These regulations require all community health centers in Indonesia to change their status to BLUDs. During this transition, the Community Health Center faced many challenges, such as preparation, financial management, technology, human resources, corruption and poor internal control, which negatively impacted the performance and survival of the Community Health Center. Therefore, this article will integrate the internal control of the Committee of Sponsoring Organizations of the Treadway Commission (COSO) into BLUD Community Health Centers so that they can resolve all their problems and improve their performance. The approach of this article uses a qualitative descriptive approach. Based on the results and discussions, COSO internal control can be implemented in BLUD community health centers. In addition, the five components of COSO internal control can increase the preparedness of community health centers, improve technology and innovation, competent human resources, reduce corruption, and increase the effectiveness of internal control so that the performance of BLUD community health centers increases. Keywords: Internal control, COSO, BLUD, Community health center